Numerical Computation of the Elasticity of Substitution - Bowley, A. L. (Review of Economic Studies, 1937)
Journal Article Numerical Computation of the Elasticity of Substitution Get access A. L. Bowley A. L. Bowley Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 5, Issue 1, October 1937, Pages 60–65, https://doi.org/10.2307/2967580 Published: 01 October 1937